Recursos avaliativos no discurso de Jair Bolsonaro: escolhas atitudinais - Santos, Marli Ferraz dos (2021)
Analyzing the politicians’ discourse has been an important issue in studies on language in today's world scenario. In a time of polarization and resurgence of extreme right-wing ideologies, the turnaround that occurred in Brazil in 2019 was remarkable for the direction of Brazilian politics and its citizens. By radically changing the ideological orientation of the Republic government, there was also the need to examine the official manifestations of the President of Brazil. Therefore, this research aims to identify, through semantic-discursive analysis, the set of attitudinal values triggered by Jair Bolsonaro in the construction of his speeches made in the first half of 2019. The theoretical apparatus that supports the analysis follows the precepts of Systemic-Functional Linguistics (HALLIDAY; HASAN 1989), more specifically the Appraisal system (MARTIN; WHITE, 2005) and the political discourse (FAIRCLOUGH 2012; WODAK 2009a; 2009b). The research corpus consists of 77 texts, composed of 57 national speeches and 20 international speeches, published on the official page of the Presidency of the Republic. The methodology initially used quantitative and later qualitative procedures and went through the following steps: a) selection of Jair Bolsonaro’s Government Plan; b) verification of the themes and topics that make up the candidate's Government Plan; c) selection of all national and international speeches published on the official page of the Presidency; d) submission of the total number of speeches to the WordList tool, in order to verify, among the topics, those that occur more than 50 times in the corpus, which resulted in the 5 topics investigated in this dissertation: defense, economics, family, fraternity and freedom; e) submission of national and international speeches to the Concordance tool to locate the 5 selected words and their cognates; f) selection and categorization of the appraisal markers from the semantic field of attitude in the concordances found; g) qualitative analysis of the results and comparison to that proposed in the Government Plan. The analysis of the corpus showed the predominance of evaluative recurrences regarding the topic of economics carried out in the semantic field of appreciation, through which the authorial voice seeks the alignment of the authorities linked to the economic area and the listeners to the set of values and beliefs manifested in the speeches. Relevant topics of the Government Plan such as health, education, fight against corruption, free press are not very frequent in the speeches of the first semester of 2019, which leads to the understanding that from the document called “The Prosperity Path”, presented to the Superior Electoral Court in the pre-campaign period, in addition to complying with a legal requirement, only two of the 67 topics covered were prioritized.